PEMBERDAYAAN EKONOMI MASYARAKAT TIRTONIRMOLO DI TENGAH PANDEMIK COVID-19 - Nursubiyantoro, Eko; Wibowo, Astrid Wahyu Adventri; Ismianti, Ismianti (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Tirtonirmolo is one of the villages from Kasihan District whose routine activities are administrative services, which are supported by Bumdes so that the economic activities of the community grow and make a positive stretch for the village economy and the welfare of the community. Such dynamic economic and governmental activities at this time suddenly seem to stop, there is no activity as usual, because of the corona virus outbreak which has changed the structure of society, both government services and the economic movement of the community. The problem of the Tirtonirmolo Village Government is that it must continue to carry out government service duties and encourage community empowerment to continue to carry out economic activities, with the guarantee that the implementation of government services and economic activities must run safely. The service activity method is to design a service information system based on the needs of the village government, design an automatic disinfectant tool to meet protocols, design a social distancing-based work environment, empower the economy by providing training in the application of information systems for products and services online so that the economy of the Tirtonirmolo community will recover as before. there was a Covid-19 outbreak. The expected output target is to restore a clean and healthy working environment and an ever increasing economic movement.